Spatiotemporal variations and the driving factors of PM2.5 in Xi’an, China between 2004 and 2018 - Abula Tuheti; Shunxi Deng; Jianghao Li; Guanghua Li; Pan Lu; Zhenzhen Lu; Jiayao Liu; Chenhui Du; Wei Wang (Ecological Indicators, 2023)
High-intensity human socioeconomic activities in Xi’an have caused fine particulate matter (PM2.5) pollution. Understanding the spatial and temporal patterns and key factors influencing PM2.5 concentration was the basic step for taking targeted measures. Thus, spatial analysis techniques are used to reveal the temporal and spatial distribution characteristics of PM2.5 in Xi’an over a long time series; wavelet analysis and Geo-detector models are applied to assess the strength of the association between meteorological and socio-economic conditions on PM2.5 concentrations. The results illustrated that the average PM2.5 concentration was 40.13 μg/m3 in 2004 and peaked at 62.06 μg/m3 in 2011, before failing to 38.77 μg/m3 by 2018. The PM2.5 concentration distribution had a characteristic of high in winter and autumn but low in spring and summer, presenting a U-shaped profile. The main distribution of PM2.5 concentrations was oriented in a northeast-southwest direction, with obvious spatial autocorrelation and spatial aggregation characteristics. The resonance cycles of the meteorological and socioeconomic elements and PM2.5 concentrations were synchronous and divergent at different scales. U-wind was the influencing factor on PM2.5 concentration with a positive correlation coefficient of 0.9. Before 2011, the interaction of temperature (Tem) and relative humidity (RH) had the greatest impact on PM2.5 concentrations. Additionally, the land use and cover change (LUCC) coupled with other factors had a large influence on PM2.5 concentrations. These relationships can shed new light on the underlying mechanisms of PM2.5 contamination at the city level, assisting relevant departments in developing effective PM2.5 pollution management strategies.